ANALISIS PERSEPSI MASYARAKAT DUNIA TERHADAP VIRTUAL YOUTUBER YANG MENAWARKAN PENGALAMAN KEKASIH - Muhammad Haikal; Bagus Prayogi; Nathanael Putra Ganatha; Muhammad Rivan Ferdiansyah; Nur Aini Rivan Rakhmawati (Universitas Muhammadiyah Gresik, 2024)
This research investigates the global public's perception of the phenomenon of Virtual YouTubers (VTubers) who offer romantic experiences such as